What Research Evidence Says about Bilingual Education - Hakuta, Kenji ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Much information of interest to bilingual education policymakers has emerged from basic research on language learning, bilingualism, and cognition. Among the conclusions drawn from it are the following: (1) bilingual education is superior to submersion education in many contexts;(2) one major bilingual education goal should be development of the full repertoire of English linguistic skills, in preparation for mainstreaming; (3) time spent learning the native language in bilingual programs is not time lost in developing English skills; (4) children can become fluent in a second language without losing the first language, and maintenance of the first language does not retard second language development; (5) there is no cognitive cost, and there may be advantages, in the development of bilingualism in children; (6) bilingual education programs should have the flexibility of adjusting to the large individual and cultural differences among children, including need for lengthy bilingual education; (7) educators should understand that for primary grade children second language learning may be a slow process and that older learners can learn languages quickly and efficiently; (8) reading should be taught in the native language; and (9) actions upgrading the status of limited-English-speaking children's culture and language contribute to their opportunities for friendship with native English-speaking children. (MSE)
ERIC Note: Paper presented at the Annual Meeting of the National Association for Bilingual Education (Chicago, IL, April 1-5, 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Bilingualism; Educational Policy; Educational Research; Educational Strategies; Elementary Secondary Education; Language Maintenance; Learning Processes; Literature Reviews; Native Language Instruction; Policy Formation; Reading Instruction; Research Utilization; Second Language Learning; Information Analyses; Speeches/Meeting Papers